Ocular surface changes in Graves' ophthalmopathy - Sun, Rou (Int J Ophthalmol, 2021)
Many patients with Graves' ophthalmopathy (GO) suffer from dry eye syndrome (DES), and this is one of the most common reasons of eye discomfort in patients with GO. The prevalence of DES in patients with GO is significantly higher than normal subjects. The ocular surface changes involving changes in tears, cornea, conjunctiva and glands occur in GO patients. However, the mechanism of how DES occurs in GO still remains unclear. In this review, the ocular surface changes were illustrated and analyzed the reasons for high prevalence of DES in GO patients.